Hyperammonemia From Ureaplasma Infection in an Immunocompromised Child. Issue 2 (March 2020) - Placone, Nicholas; Kao, Roy L.; Kempert, Pamela; Ruiz, Maritza E.; Casillas, Jacqueline N.; Okada, Maki; Gibson, James B.; Maggi, Carlos; O'Brien, Kevin; Nattiv, Roy; Gallant, Natalie M.; Abrams, Stephanie H.
Abstract : Idiopathic hyperammonemia is a rare, poorly understood, and often lethal condition that has been described in immunocompromised patients. This report describes an immunocompromised patient with acute myelogenous leukemia who developed persistent hyperammonemia up to 705 µmol/L (normal, 0 to 47 µmol/L) refractory to multiple different therapies. However, after beginning azithromycin and then doxycycline therapy for Ureaplasma species infection, the patient showed immediate and sustained clinical improvement and resolution of ammonia levels. Recognizing disseminated Ureaplasma species infection as a potential cause of idiopathic hyperammonemia, an unexplained, often fatal condition in immunocompromised patients, and empirically treating for this infection could potentially be lifesaving.